2020
DOI: 10.3390/ijerph17165803
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the ‘Optimising the Health Extension Program’ Intervention in Ethiopia: A Process Evaluation Using Mixed Methods

Abstract: An intervention called ‘Optimising the Health Extension Program’, aiming to increase care-seeking for childhood illnesses in four regions of Ethiopia, was implemented between 2016 and 2018, and it included community engagement, capacity building, and district ownership and accountability. A pragmatic trial comparing 26 districts that received the intervention with 26 districts that did not found no evidence to suggest that the intervention increased utilisation of services. Here we used mixed methods to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, when combined in the upscaled intervention, there was no effect. A process evaluation to examine the quantity and quality of what was implemented showed that lack of effect could partly be attributed to delays in implementation of some initial activities that would create the condition for the successful implementation of the next activity, interruptions and an overall short implementation period of a complex intervention [ 32 ]. This could shed light on the fidelity of the implementation, the context in which this complex intervention was delivered, and explain why it did not work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when combined in the upscaled intervention, there was no effect. A process evaluation to examine the quantity and quality of what was implemented showed that lack of effect could partly be attributed to delays in implementation of some initial activities that would create the condition for the successful implementation of the next activity, interruptions and an overall short implementation period of a complex intervention [ 32 ]. This could shed light on the fidelity of the implementation, the context in which this complex intervention was delivered, and explain why it did not work.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of effect could partly be attributed to delays, interruptions and an overall short implementation period of a complex intervention. Complex interventions that aim at behaviour changes in the health services as well as in care seeking for sick children may need an extended implementation period [ 32 ]. Previous Ethiopian studies have shown that the health extension workers were insufficiently prepared for all the tasks that fall within their scope of work [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complex interventions that aim to change health services and care-seeking for sick children may need an extended implementation period. 45 Lack of effect could also be due to some of these contextual factors necessary for improving quality.…”
Section: Discussionmentioning
confidence: 99%
“…The strategies included home-based preventive and curative child health services to enhance equity in coverage [ 16 ]. Various contextual factors limited the scale-up of these outreach activities [ 17 ]. Services provided in outreach activities had greater equity in coverage, although these were highly affected by geographical characteristics [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%